The burden of menstrual irregularities among women living with HIV in Nigeria: a comprehensive review - Bonaventure Michael Ukoaka; Adejumoke Hephzibah Abiodun; Faithful Miebaka Daniel; Monica Anurika Gbuchie; Olalekan John Okesanya; Tajuddeen Wali Adam; Ikponmwosa Jude Ogieuhi; Keziah Uchechi Ajah (BMC, 2024)
Abstract Background Menstrual irregularities significantly distress women living with HIV (WLHIV), impacting their reproductive health and quality of life. Although the underlying mechanism remains inconclusive, studies have outlined possible contributory factors. This narrative review explores the burden of menstrual irregularities and associated hormonal dysregulation among women living with HIV in Nigeria. It synthesises data from studies to present an overview of the prevalence, patterns, potential etiology, and impacts of menstrual irregularities among WLHIV. Main body A literature search across electronic databases such as PubMed, Google Scholar, and Web of Science was conducted, and information was extracted and synthesized to delineate the burden of menstrual irregularities in WLHIV. Eligibility criteria included original studies assessing the prevalence, aetiology, and impact of menstrual abnormalities among WLHIV in Nigeria. A narrative data synthesis approach utilized common themes and key concept extraction, including identifying patterns in the literature to present specific trends such as prevalence, patterns, etiology, and determinants. Menstrual irregularities were found to be prevalent among Nigerian WLHIV, varying from 29 to 76% across different regions, exceeding reports of similar studies in developed nations. Similarly, menstrual disorders including amenorrhea, oligomenorrhea, and polymenorrhea, were attributed to factors like HIV acquisition, antiretroviral therapy, low body mass index, and hormonal imbalances. Low CD4 count and high viral load with associated complications have been identified as major contributing factors. Distortion of the hypogonadal-pituitary-ovarian axis by viral-induced pro-inflammatory cytokines such as tumor necrosis factor-alpha (TNF-α), interleukin-1 (IL-1), interleukin-6 (IL-6), and interferon-gamma (IFN-γ) may disrupt the hormonal balance necessary for regular menstrual cycles. Fluctuating levels of follicle-stimulating hormone (FSH), luteinising hormone (LH), estradiol, and prolactin have been reported among WLHIV. Although adherence to antiretroviral therapy has offered immense relief, its direct therapeutic effects on menstrual irregularities are inconclusive.. Conclusions This study highlights the burden of menstrual disorders among WLHIV. It underscores the interplay between clinical, therapeutic, and client-associated factors as determinants of these abnormalities. Exploring associated complications like secondary infertility, reduced bone mineral density, and resultant osteoporosis, mirrors the significant impact of menstrual and hormonal irregularities on the reproductive health and quality of life of WLHIV.